Mathematics - Trigonometric Identities - Reiny

Mathematics - Trigonometric Identities - Reiny, Friday, November 9, 2007 at 10:30pm

(sinx - 1 -cos^2x) (sinx + 1 - cos^2x)

should have been

(sinx - 1 + cos^2x) (sinx + 1 - cos^2x) and then the next line should be

sin^2x + sinx - cos^2xsinx - sinx - 1 + cos^2 x + cos^2xsinx - cos^4x
= cos^2 x - cos^4 x
= RS

an easier way would have been

LS = sin^2x(1-sin^2x) by common factor
=sin^2x(cos^2x)

RS = cos^2x(1-cos^2x) also by common factor
=cos^2x(sin^2x)
= LS

--------------------

What happened to the negative in the first line?

You wrote:

an easier way would have been

LS = sin^2x(1-sin^2x) by common factor
=sin^2x(cos^2x)

--

Shouldn't it be LS = sin^2x (-sin^2x) ?

And for my way ...

You wrote:

(sinx - 1 -cos^2x) (sinx + 1 - cos^2x)

should have been

(sinx - 1 + cos^2x) (sinx + 1 - cos^2x) and then the next line should be

sin^2x + sinx - cos^2xsinx - sinx - 1 + cos^2 x + cos^2xsinx - cos^4x
= cos^2 x - cos^4 x
= RS

--

and I'm asking why is the "cos^2x" a negative from "sinx - 1 + cos^2x"?

This line, "sin^2x + sinx - cos^2xsinx - sinx - 1 + cos^2 x + cos^2xsinx - cos^4x" ----> I get "sin^2x + sinx - cos^2xsinx - sinx - 1 + cos^2x + cos^2xsinx + cos^2x - cos^4x" ----> I get an extra "cos^2x" ...

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩
  1. sin^2x - sin^4x = cos^2x - cos^4x

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  2. Ok, let's start from the beginning

    sin^2x - sin^4x = cos^2x - cos^4x

    LS = (sinx - sin^2 x)(sinx + sin^2 x)

    then you had:
    (sinx - 1 -cos^2x) (sinx + 1 - cos^2x)

    I will put in the in-between step

    =(sinx - (1 -cos^2x)) (sinx + 1 - cos^2x)

    = (sinx - 1 + cos^2x) (sinx + 1 - cos^2x)
    = sin^2x + sinx - cos^2xsinx - sinx - 1 + cos^2 x + cos^2xsinx + cos^2 x - cos^4x
    (and yes, you are right, I left out a +cos^2 x , so.......

    = sin^2x+cos^2x + sinx-sinx - 1 + cos^2xsinx-cos^2xsinx + cos^2 x - cos^4 x
    = 1 + 0 - 1 + 0 + cos^2 x - cos^4 x
    = cos^2 x - cos^4 x
    = RS

    For my second solution I worked on both the LS and the RS, reaching the same expression at both ends.

    Surely your teacher must have shown you that as an acceptable method.

    Here is what you wrote:

    "hat happened to the negative in the first line?"

    regarding:

    LS = sin^2x(1-sin^2x) by common factor
    =sin^2x(cos^2x)

    didn't you recognize the replacement of
    1 - sin^2 x with cos^2 x ???

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  3. I see it now, thanks

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math, please help

    Which of the following are trigonometric identities? (Can be more then one answer) tanx cosx cscx = 1 secx-cosx/secs=sin^2x 1-tanxtany=cos(x+y)/cosxcosy 4cosx sinx = 2cosx + 1 - 2sinx Find all solutions to the equation cosx

  2. Math

    If sin(x) = 1/3 and sec(y) = 29/21 , where x and y lie between 0 and π/2, evaluate the expression using trigonometric identities. (Enter an exact answer.) cos(2y)

  3. math trigonometry

    Simplify the following expression to a single trigonometric term sin(360-x)*tan(-x)/cos(180 x)*(sin^2A cos^2A) answer= -sinx*-tanx/cosx*(1) after that how do i continue?

  4. Trig

    How do you express sin4x as a trigonometric funcition of x using the identities? I think that you are supposed to start with the sine sum identity and then use the double angle identities for sin2A and cos2A, but after that I get

  1. Trig.......

    I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30º, the two sides are not equal, they differ by 1 oh , thank you Mr

  2. Math

    Mrs. Hart, at age 65, can expect to live for 25 years. If she can invest at 5% per annum compounded monthly, how much does she need now to guarantee herself $900 every month for the next 25 years? math - Reiny, Friday, April 3,

  3. Pre-Calc : Verify the Identity

    Verify the Identity: sin(x+π)/cos(x+3π/2) =tan^2x-sec^2x I've done: sinxcosπ+cosxsinπ / cosxcos(3π/2) - sinxsin(3π/2) sinx(-1) + cosx(0) / cosx(0)- sinx(-1) -sinx/sinx What do I do from here? Or what did I do wrong?

  4. Math

    Use the given function value(s), and trigonometric identities(including the cofunction identities), to find the indicated trigonometric function. sec θ = 5 a) cos θ = 1/sec θ = 1/5 b) cot θ = cos θ/sin θ =cosθ/cos(90-θ) I

  1. Trig

    Simplify sin x cos^2x-sinx Here's my book's explanation which I don't totally follow sin x cos^2x-sinx=sinx(cos^2x-1) =-sinx(1-cos^2x) =-sinx(sin^2x) (Where does sine come from and what happend to cosine?) =-sin^3x

  2. Pre-Calculus

    This question has me stuck. Use the Pythagorean identity sin^2 Θ + cos^2 Θ = 1 to derive the other Pythagorean identities, 1 + tan^2 Θ = sec^2 Θ and 1 + cot^2 Θ = csc^2 Θ. Discuss how to remember these identities and other

  3. Math

    (sinx - cosx)(sinx + cosx) = 2sin^2x -1 I need some tips on trigonometric identities. Why shouldn't I just turn (sinx + cosx) into 1 and would it still have the same identity?

  4. math

    Proving Trigonometric Identities 1. sec^2x + csc^2x= (sec^2 x)(csc^2 x) 2. sin ^3 x / sin x - cos 3x / cos x = 2 3. 1- cos x/ sin x= sin x/ 1+ cos x 4. 2 sin x cos ^2 (x/2)- 1/x sin (2x) = sinx 5. cos 2 x + sin x/ 1- sin x= 1+ 2

View more similar questions or ask a new question.